Assessment of index-based traffic noise annoyance level at major road intersections in a tourist city: A case study towards environmental sustainability - Zullyadini bin A. Rahaman (Tanjung Malim, 2024)
Assessment of index-based traffic noise annoyance level at major road intersections in a tourist city: A case study towards environmental sustainability by Zullyadini bin A. Rahaman